Kinesiophobia, physical activity levels and barriers in breast cancer patients, survivors, and healthy controls: a case-control analysis - Nuray Alaca; Kubra Turker Karayazi; Dilek Cagri Arslan; Meryem Bektas Karakus; Uras, Cihan (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate kinesiophobia, physical activity levels and barriers to physical activity in women with breast cancer and breast cancer survivors. Method: The case-control study was conducted at the Breast Clinic of Acibadem Maslak Hospital, and the Department of Physiotherapy and Rehabilitation at Acibadem Mehmet Ali Aydinlar University, Turkey, from October 2021 to July 2022, and comprised patients with breast cancer in group A, breast cancer survivors in group B and healthy controls in group C. The primary outcome measures were physical activity levels, barriers to physical activity and kinesiophobia levels, while the secondary outcome measures were levels of anxiety, depression, fatigue and quality of life. Data was collected using standard tools. Data was analysed using SPSS 22. Results: Of the 212 women, 70(33%) were in group A with mean age 50.71±11.30 years, 70(33%) in group B with mean age 47.64±9.85 years, and 72(34%) in group C with mean age 47.03±7.48 years. Group C had better physical activity levels, fatigue and quality of life scores than the other groups, but it had worse perceptions of physical activity and more individual, psychosocial and environmental barriers to physical activity compared to the other groups (p<0.05). Group A had more barriers to exercise related to fear of overall body pain, poor balance, fear of falling and fear of feeling worse post-exercise compared to the other groups (p<0.05). Group B subjects were more afraid that lymphedema might be exacerbated if they exercised (p<0.05). Conclusion: Women with breast cancer and breast cancer survivors had worse scores for physical activity levels, fatigue and quality of life compared to the healthy controls. All three groups had a variety of barriers to physical activity. Key Words: Breast neoplasms, Healthy volunteers, Kinesiophobia.